Inhibitors of HIV-Protease from Computational Design. A History of Theory and Synthesis Still to be Fully Appreciated - Berti, Federico; Frecer, Vladimir; Miertus, Stanislav (Current Pharmaceutical Design, 2014)
Despite the fact that HIV-Protease is an over 20 years old target, computational approaches to rational design of its inhibitors still have a great potential to stimulate the synthesis of new compounds and the discovery of new, potent derivatives, ever capable to overcome the problem of drug resistance. This review deals with successful examples of inhibitors identified by computational approaches, rather than by knowledge-based design. Such methodologies include the development of energy and scoring functions, docking protocols, statistical models, virtual combinatorial chemistry. Computations addressing drug resistance, and the development of related models as the substrate envelope hypothesis are also reviewed. In some cases, the identified structures required the development of synthetic approaches in order to obtain the desired target molecules; several examples are reported.
Keywords: pseudopeptide synthesis